Genomics of pattern recognition receptors : applications in oncology and cardiovascular diseases - Kutikhin, Anton G. (Springer Basel, 2013)
This book offers comprehensive information on the polymorphisms of genes encoding pattern recognition receptors (PRRs). Following a short description of the general role of PRRs in the immune system, the structure and function of Toll-like and NOD-like receptors are examined in detail. The main focus is on the role of inherited variation in PRRs and their correlation to cancer and cardiovascular diseases. A review of all epidemiological investigations is included, and a concept of genomic risk markers for the prevention of various diseases is also discussed.